Efficient Structures Of The Hierarchical Organization Of Management In The Firm. - Kamil, Anton Abdulbasah (2003)
In this paper, economic explanation of the hierarchical organization of management in the firm is provided based on the analysis of organizational aspects of data processing in decision making. The paper shows that decreasing returns to scale in information processing is a necessary condition for hierarchical organization of management in business firms. However, decentralization of decision-making is desirable only if an additional (sufficient) condition is satisfied, Le., if the information workload of the decision-making sector is sufficiently large.